Constructing and Resisting Modernity Madrid 1900-1936 - Larson, Susan (La Casa de la Riqueza. Estudios de la Cultura de España, 2011)
This book studies the urban spaces imagined by the technocrats who had the power to shape Madrid between 1900 and 1936 and relates them to the fiction of authors who responded by creating utopian and dystopian narratives